A Sustainable and Economically Recycling Real Estate Development Project: A Case Study for Istanbul Park - Demir, H.; Sanli, F. Balik; Gur, M.; Goksel, C. (SPRINGER-VERLAG BERLIN, 2011)
Nowadays, together with the globalization fact, an effort is given to rebuild the environment. These models have been developed without taking natural and ecological corruption in to consideration. They just take into account the economical growth, leading to economical and cultural demolition. In order to balance economical development and ecology, a sustainable development must be reassured. If real estate development projects are investigated, one usually observes that the balance between urbanization and sustainability is not protected. Since the importance of land and land management has not been understood well, those implemented projects without required pre-evaluations have caused problems in terms of urbanization and urban economy. In this study, Formula One (Fl) Istanbul Park Circuit real estate development project is evaluated considering relation of urbanization and sustainability. Evaluation of the project was made in terms of economy, changes in land use types, effects on real estate prices and contributions to the benefits of society. The changes of land use types were monitored using the time series of high-resolution satellite data, namely QUICKBIRD and IKONOS. Change detection methods were used for the analysis of similar to 50 km(2) area. Results show that 2,826 ha of the area, mainly having agricultural field land use types, appears to be open to urbanization. 1,268 ha area of green land including endemic vegetations is, under pressure of uncontrolled urbanization.
Keywords: Land use change; Sustainable Real Estate Development; Monitoring Urbanization; F1 Istanbul Park Circuit; LAND-USE CHANGE; SYSTEM; IMAGE; COVER; Environmental Sciences & Ecology